Evaluation in Canada - Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2005)
The Canadian provinces continue to be a source of evaluation-related activities and events such as Evaluation 2005, Beaulac, Goodine, and Aubry's work on a reportcard of homelessness in Ottawa, the 2005 International Program for Development Evaluation jointly sponsored by the World Bank Group and Carleton University, and the Canadian Evaluation Society Student Case Competition and Paper Contest, to name but a few. For those interested in detailed information on these and other Canadian evaluation news and events please visit the Canadian Evaluation Society Website.